Psychological Dynamics of Parents: Educational Adaptations of Children with Special Needs in Schools and Homes - Rositas; Helen Fitriani; Aat Muslihat; Imam Tabroni (International Journal of Integrative Sciences, 2023)
The aim of this research is to find the psychological dynamics of parents who have children with special needs. Disclosure, analysis, and interpretation methods use the quality of communication, observation, and interviews with all parents who have children with special needs at SLB N 1 Purwakarta. The results showed that the psychology of parents experienced high shocks. At the beginning of the detection of the level of special needs of children, parents seemed not to accept this fact. In the next stage, parents find other parents who are in the same boat. At this stage the psychological adaptation process of parents enters the DABDA process. First, Denial. Parents cannot accept the fact that their child has special needs. Second, angry. The anger was aroused by the fact that it actually happened. Third, Bargaining. Parents have started to make peace with themselves and the facts that must be accepted. New parents realize that everything happens by His power. Fourth, Depression. At this stage parents and their children withdraw from the environment, and Fifth, Acceptance. The process of adaptation and self-acceptance to be able to adapt and communicate with others